LG Household & Health Care: Building a High-Performing Organization - Lee, Seung Joo (KDI School of Public Policy and Management, 1999)
LG Household & Health Care (LGHH) is Korea’s leading producer of household goods, cosmetics, and pharmaceuticals products. The case describes the company’s growth history, the performance crisis it faced in the early 1990s, and the leadership actions taken by President Cho Myung-Jae to turnaround the company and build a high-performing organization. This case, based on original field data, illustrates the importance of top management leadership in corporate transformation, and some of the key success factors in initiating and sustaining a major change program.